If a polynomial function has a zero at 1, one of its factors is (x-1), since when
we know x=1.
So there are three factors of this polynomial. Write them beside each other to write the function in factored form: y = (x-1)(x-2)(x-5).
And start multiplying!
y = (x2-3x+2)(x-5)
Then keep multiplying:
y = x3-3x2+2x-5x2+15x-10
And combine like terms to get the final answer:
Note: the leading coefficient is already 1. If you wanted a different coefficient, you would just multiply each term by that number.
I hope this helps!